Acute blood transfusion reactions in a tertiary care hospital in Pakistan ‐ an initiative towards haemovigilance. Issue 4 (29th May 2018) - Borhany, M.; Anwar, N.; Tariq, H.; Fatima, N.; Arshad, A.; Naseer, I.; Shamsi, T.
SUMMARY: Objective: In this study, we report acute blood transfusion reactions at our hospital, compare our analysis with the reported data and identify areas for improvement. Background: Haemovigilance programmes have been implemented in many countries, and adverse events associated with blood transfusion are published in their annual reports. Pakistan has no current established programme. Material and Methods: A cross‐sectional study was conducted, and all adverse reactions reported to the blood bank from January 2014 to March 2016 were included. An adverse response in the patient, related to administration of blood (within 24 h), was considered an immediate transfusion reaction. Results: During the study period, 20 956 blood components were issued. A total of 32 (0·15%) adverse reactions were documented. Allergic reactions were the most common adverse event observed in 15 (46·8%) of the cases. Febrile non‐haemolytic transfusion reaction (FNHTR) was the second most common reaction seen in nine (28%) followed by bacterial contamination in four (12·5%) and acute haemolytic reaction in two (6·2%) of the cases. Conclusion: The low incidence indicates underreporting and the need for a formal haemovigilance system. International benchmarking between different medical systems is helpful to identify areas in the transfusion process that have to be changed to improve transfusion safety.